Unmet needs in emergency department patients as an important aspect of the increasing number of hospitalizations - Szwamel, Katarzyna; Kurpas, Donata (Family Medicine & Primary Care Review, 2017)
Background. Unmet needs in the medical care of high-need patients may increase costs due to the use of emergency departments (EDs) instead of primary care. Objectives . To establish the possible correlation between the unmet needs of patients and the number of hospitalizations, and the probability of influence of the former aspect on the latter, and to analyze the level of satisfied needs of ED patients in relation to sociodemographic data. Material and methods . An original questionnaire and a modified version of the Camberwell Assessment of Need Short Appraisal Schedule (CANSAS) were used to assess the level of satisfaction of the social, medical, psychological and environmental needs of 150 ED patients. Results . Most respondents were women (54%; 81/150) of a median age of 44.5 (range: 18–87). Nearly a half of the patients (48%; 72/150) were treated due to chronic diseases. A high Camberwell index (above 0.825) was negatively correlated with the total number of hospitalizations in a three-year period (r = -0.37; p < 0.001). The chance of hospitalization in people with a low Camberwell index (below 0.825) was 3 times higher than in those with higher values (OR 0.36; 95% CI 0.17–0.72). The highest level of satisfied needs was obtained by people aged 38–47, with higher education, married, living in a relationship, declaring a very good material status. Conclusions . An ED visit prevention program should include the target primary care patient groups with the highest chance of hospitalization, in particular: people aged over 67, with chronic diseases, with primary education only, widows/widowers, declaring a poor material status and living alone.